Dietary intakes and the risk of low energy availability in male and female advanced and elite rock climbers - Monedero, J.; Duff, C.; Egan, B. (The Journal of Strength and Conditioning Research, 2023)
There is a culture among rock climbers of striving to maintain low body mass and percentage body fat to enhance performance. Diet practices based on this belief might lead to increased risk of low energy availability (LEA) or eating disorders (EDs). Twenty-five advanced or elite rock climbers (male, n = 14; female, n = 11) had body composition measured, completed 4-day food intake and physical activity diaries while wearing an accelerometer and heart rate monitor, and completed the Eating Attitudes Test (EAT)-26 and the Low Energy Availability in Females Questionnaire (LEAF-Q; n = 11 female subjects only). EAT-26 scores of 3.5 (1.8, 7.0) [median (IQR)] and 9.3 ± 6.4 (mean ± SD) for male and female subjects, respectively, indicated low risk of ED in this cohort, but 4 female subjects were at high risk of LEA according to LEAF-Q scores. Suboptimal (<45 kcal·kg·FFM-1·d-1) and LEA (<30 kcal·kg·FFM-1·d-1) were evident in 88 and 28%, respectively, of climbers. However, only the female climbers had energy intakes (1775 ± 351 kcal·d-1) significantly lower than their calculated energy requirements (2056 ± 254 kcal·d-1; p = 0.006). In all subjects, carbohydrate intakes were lower (male subjects: 3.8 ± 1.2 g·kg-1·d-1, p = 0.002; female subjects: 3.4 ± 0.7 g·kg-1·d-1, p < 0.001), and fat intakes were higher (male subjects: 1.6 ± 0.5 g·kg-1·d-1, p < 0.001; female subjects: 1.4 ± 0.4 g·kg-1·day-1, p < 0.001) than current sports nutrition recommendations, and inadequate intakes of calcium, magnesium, and vitamin D were observed. Female subjects specifically had lower than recommended intakes of protein and iron. These results show that advanced and elite rock climbers have a high prevalence of LEA and have a risk of having nutritional deficiencies as result of their diet.